Perancangan Interior Modular pada Residential Space Tipe Studio - Pricillia Eka Cristi; Yusita Kusumarini; filipus priyo suprobo (Intra, 2014)
Modular Interior for Studio Residential Space is a design project of Simple Residential Space which only has one room inside (beside the bathroom). This design will be a solution for a Simple Residential Space which only has a room by maximizing that one room for multi function and activity and giving privacy to the user. The Facility expected as the product is a modular furniture which is a combination of bedroom, dining room, living room, family space, and also the kitchen. By a precise placement of function and a smart design, this furniture will comfort the owner with such an affordable price to own.